(untitled) (Journal of Pharma Insights and Research, 2025)
The aim of this research work was to develop biodegradable medicated sutures from banana fibers, using natural antimicrobial agents including Aloe vera, Neem, and Turmeric. A Central Composite Design was used to evaluate four critical parameters: extract concentration, coating duration, drying temperature, and extract solution pH. The optimization process identified optimal conditions at 3% extract concentration, 30 minutes coating time, 40°C drying temperature, and pH 6, yielding maximum biological performance. The evaluation of antimicrobial activity showed significant inhibition zones against Staphylococcus aureus (18.58 mm) and Candida albicans (17.88 mm). The quadratic model showed high statistical significance with an R² value of 0.9511, confirming robust experimental design. The formulated sutures exhibited enhanced tensile strength, controlled drug release, and appropriate biodegradation rates. FTIR studies confirmed successful coating of the natural extracts on the banana fibers. The optimized sutures demonstrated significant antimicrobial, anti-inflammatory, and antioxidant properties, making them suitable for cosmetic and minor surgical procedures. The study establishes a promising approach for developing sustainable, biocompatible sutures with improved wound-healing properties using natural materials and bioactive compounds.